Analisis Digital-Based Brand Image Dalam Meningkatkan Market Competitiveness Rumah Sakit Khusus Mata Medan - Aida Sulisna; Sri Agustina Meliala; Muhammad Fauzi (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2026)
Digital transformation in the healthcare sector has significantly reshaped hospital marketing strategies and brand positioning. Digital-based brand image has become a strategic factor in enhancing market competitiveness, particularly in specialized hospitals. This study aims to analyze the influence of digital-based brand image on the market competitiveness of Rumah Sakit Khusus Mata Medan. This research employed a quantitative approach with an explanatory cross-sectional design. A total of 150 respondents were selected using purposive sampling, consisting of outpatients who had accessed hospital information through digital platforms. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using simple linear regression. The results indicate that digital-based brand image has a positive and significant effect on market competitiveness (β = 0.68; p < 0.001), with a coefficient of determination (R²) of 0.46. These findings suggest that website quality, credibility of digital information, management of online reviews, and social media consistency contribute to increasing patient loyalty, revisit intention, and perceived competitive advantage. Managerially, this study highlights the importance of integrating digital branding strategies with clinical service quality improvement to strengthen hospital positioning and organizational sustainability in the era of digital transformation